1998
DOI: 10.1103/physrevd.57.2500
|View full text |Cite
|
Sign up to set email alerts
|

Quantum bubble nucleation beyond the WKB approximation: Resummation of vacuum bubble diagrams

Abstract: On the basis of Borel resummation, we propose a systematical improvement of bounce calculus of quantum bubble nucleation rate. We study a metastable super-with an attractive interaction. The validity of our proposal is tested in D = 1 (quantum mechanics) by using the perturbation series of ground state energy to high orders. We also present a result in D = 2, based on an explicit calculation of vacuum bubble diagrams to five loop orders.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In the above, we found that at 1/g ≈ 1, there exists a crossover boundary separating two distinctive regimes. Our result supports the previous proposal of [13]. The authors calculated the effective potential, and found that for g > 1.17, the potential barrier is smeared out by quantum fluctuations.…”
Section: Analytic Continuation To G < 0: False-vacuum Decay Ratesupporting
confidence: 93%
See 4 more Smart Citations
“…In the above, we found that at 1/g ≈ 1, there exists a crossover boundary separating two distinctive regimes. Our result supports the previous proposal of [13]. The authors calculated the effective potential, and found that for g > 1.17, the potential barrier is smeared out by quantum fluctuations.…”
Section: Analytic Continuation To G < 0: False-vacuum Decay Ratesupporting
confidence: 93%
“…So far, several ab initio approaches have been proposed in order to calculate the decay rate beyond semiclassical approximation. In particular, the φ 4 model in 0 + 1 dimension has come under through investigation [11,12,13,14], while the extension to manybody case remains unsuccessful. In the present paper, by means of the strong-coupling expansion, we studied the (1 + 1)-dimensional lattice φ 4 model (1).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations